Risk perception of severity or death from COVID-19: a systematic review of the factors associated - Rosa, Rander Junior; Andrade, Rubia Laine de Paula; Perticarrara Ferezin, Letícia; de Campos, Mônica Chiodi Toscano; Moura, Heriederson Sávio Dias; Berra, Thais Zamboni; Ribeiro, Natacha Martins; Teibo, Titilade Kehinde Ayandeyi; Vinci, André Luiz Teixeira; Mendes Delpino, Felipe; Torres, Miguel Ángel Fuentealba; Arcêncio, Ricardo Alexandre (Frontiers in Public Health, 2025)
BackgroundHealth risk perception and factors associated with the severity or death from COVID-19 were key elements that influenced individuals' protective behaviors during the pandemic. Understanding these perceptions is crucial for public health guidelines that encourage preventive measures and improve an outbreak response strategy. Thus, this systematic review aimed to identify factors associated with the perception of risk of severity or death from COVID-19.MethodsA systematic review was conducted with an article search performed in March 2024 across five databases, utilizing both controlled and free vocabulary. Studies published from 2020 onward were included. Two reviewers independently selected articles, with disagreements resolved by a third reviewer. The data were extracted using a structured form, and the findings were synthesized narratively. The studies included in the review underwent a methodological quality assessment using tools proposed by the Joanna Briggs Institute.ResultsNineteen articles were included in the review. Among the factors most frequently associated with the perception of severe illness or death from COVID-19 were advanced age, female gender, personal experience or witnessing of adverse COVID-19 outcomes, the presence of chronic non-communicable diseases, and lower educational attainment.ConclusionThe study highlights that the perception of risk for COVID-19 severity or death varied according to age, gender, and prior experiences with the disease. Such findings can guide healthcare practices and contribute to the formulation of public policies, strengthening responses to future public health crises.Systematic review registrationidentifier CRD42024444734, https://www.crd.york.ac.uk/PROSPERO/view/CRD42024444734.